Highly active and selective photochemical reduction of CO2 to CO using molecular-defined cyclopentadienone iron complexes. Issue 54 (15th June 2016) - Rosas-Hernández, Alonso; Alsabeh, Pamela G.; Barsch, Enrico; Junge, Hernrik; Ludwig, Ralf; Beller, Matthias
Abstract : Highly active and selective visible-light-driven CO2 reduction to CO catalyzed by well-defined cyclopentadienone iron complexes. Abstract : Herein, we report highly active (cyclopentadienone)iron–tricarbonyl complexes for CO2 photoreduction using visible light with an Ir complex as photosensitizer and TEOA as electron/proton donor. Turnover numbers (TON) of ca. 600 (1 h) with initial turnover frequencies (TOF) up to 22.2 min −1 were observed. Operando FTIR measurements allowed for the proposal of a plausible mechanism for catalyst activation.